Greece in the 1940s : cccupation and civil war in digital culture, screen media, and the arts - Savvides, Leandros; Ferra, Ioanna (Digital activism and society: politics, economy and culture in network communication, 2024)
During the 1940s, Greece experienced some of the most significant moments in the contemporary history of the country, defining the socio-political environment to this day. Greece in the 1940s presents a deep dive into this time in history, as seen through digital media, films, journalism and art. Considering the impact of the 1940s on influencing and polarising Greek political culture to this day, this edited volume brings together academics, researchers, and practitioners to investigate historical continuities and discontinuities in the public discourse and the creation of diverse sets of opinions around conflict in Greece and internationally. The chapter authors explore the construction of collective memory through different forms of media, concentrating on some of the most significant historical events of contemporary Greek history. Different forms of media contributing to the construction of public discourse and collective memory are explored, including films, digital media, journalism, art, memory, and the representation of the 1940s, offering a comprehensive study of the digital history and development of Greece.